Bartonella massiliensis sp. nov., a new bacterial species isolated from an Ornithodoros sonrai tick from Senegal. (November 2019) - Medkour, H.; Lo, C.I.; Anani, H.; Fenollar, F.; Mediannikov, O.
Abstract: Bartonella massiliensis sp. nov., strain OS09 T (= CSURB624 T = DSM 23169), is the type strain of Bartonella massiliensis sp. nov., a new species within the genus Bartonella. It was isolated from a soft tick, Ornithodoros sonrai, vector of recurrent fever collected from Senegalese domestic rodent burrows. This strain is an aerobic, rod-shaped and Gram-negative bacterium. On the basis of taxonogenomic approach, we propose the creation of Bartonella massiliensis sp. nov.